Calcium stability of calcium-fortified ready-to-drink non-dairy chocolate beverage - Sioson, Israel Ellis Toledo (2000)
ABSTRACT In response to the growing public awareness and concern about osteoporosis and other calcium deficiencies, formulating a calcium-fortified ready-to-drink nondairy beverage that will be generally consumed proves to be timely. To produce a "very much liked" and physically stable ready-to-drink nondairy chocolate beverage, optimum ingredient levels were used: 87.75 water, 5.17% milk substitute, 3.39% chocolate syrup, 1.66% artificial flavor, 0.80% cocoa powder, 0.67% sugar, 0.40% stabilizer and 0.22% emulsifier. Among six calcium salts used to fortify the control formulation, and after production and sensory evaluation of batches of calcium-fortified ready-to-drink nondairy chocolate beverage, calcium triphosphate was chosen as the fortificant. Upon upscaling of production, no significant difference was found between calcium-fortified samples from laboratory and bench scales. After three production runs at bench scale, reproducibility of the beverage was confirmed and specifications of the process and formulation were developed. Moreover, quality assessment revealed that both unfortified and calcium-fortified samples were insignificantly different in terms of physico-chemical properties except for soluble solids, viscosity, crude fat and ash contents.Likewise, both were microbiologically stable and reasonably inexpensive. Finally, AAS analysis on the calcium stability of calcium-fortified chocolate beverage stored for one week showed 84.64% retention, yet the beverage still meets 56.42% of the 1998 updated Philippine RDA for calcium.